2015
DOI: 10.1021/acsmedchemlett.5b00176
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Pyrazolo[1,5-a]pyridine-3-carboxamides as Novel Antitubercular Agents

Abstract: A series of pyrazolo[1,5-a]pyridine-3-carboxamide derivatives were designed and synthesized as new anti-Mycobacterium tuberculosis (Mtb) agents. The compounds exhibit promising in vitro potency with nanomolar MIC values against the drug susceptive H37Rv strain and a panel of clinically isolated multidrug-resistant Mtb (MDR-TB) strains. One of the representative compounds (5k) significantly reduces the bacterial burden in an autoluminescent H37Ra infected mouse model, suggesting its promising potential to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 23 publications
0
76
0
Order By: Relevance
“…17 As summarized in Figure 2, the 4-aryl- N -Boc-piperidine adduct was obtained in good yield using the optimized oxalate coupling conditions. After removal of the Boc group, the secondary amine was subsequently coupled with 4-cyanophenyl bromide using our previously published metallaphoto amination protocol 18 to deliver precursor 46 in excellent yield.…”
mentioning
confidence: 97%
“…17 As summarized in Figure 2, the 4-aryl- N -Boc-piperidine adduct was obtained in good yield using the optimized oxalate coupling conditions. After removal of the Boc group, the secondary amine was subsequently coupled with 4-cyanophenyl bromide using our previously published metallaphoto amination protocol 18 to deliver precursor 46 in excellent yield.…”
mentioning
confidence: 97%
“…The in vitro potency against replicating H37Rv-Mtb, non-replicating H37Rv-Mtb (LORA), toxicity to mammalian cells (VERO) and aqueous solubility were determined for these compounds and a positive control, Q203 ( Table 1). The ITA class showed very similar SAR trends to those observed with very structurally similar imidazo[1,2-a]pyridine-3-carboxamines [9,10,15,17,18] and pyrazolo[1,5-a]pyridine-3-carboxamides [29][30][31]. For instance, the most potent compounds were often the most lipophilic compounds as exemplified by ND-11543 and ND-11564 (clogP of 5.4 and 6.6, respectively) whereas polar compounds like ND-11903 and ND-12015 (clogP of 2.4 and 2.1, respectively) were >100-fold less active by comparison (Table 1).…”
Section: Resultsmentioning
confidence: 53%
“…The IPAs, including Q203 (1, Fig 1), target the electron transport chain, specifically at QcrB, a component of the terminal cytochrome oxidase [16,17]. Various scaffolds have emerged that target QcrB (Fig 1) [ [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], two classes, imidazo[2,1-b]thiazole-5-carboxamides (ITAs) (2) [26][27][28] and pyrazolo [1,5-a] pyridine-3-carboxamides (3) [28][29][30][31], bear the greatest structural homology and potency relative to the IPAs (Fig 1). We have disclosed the impressive in vitro properties of various ITAs, including low nanomolar potency against replicating and drug-resistant Mtb strains and low cyctotoxicity [26,27], as exemplified by ND-11543 (2).…”
Section: Introductionmentioning
confidence: 99%
“…observed that similar type of compounds having pyrazolo[1,5‐ a ]pyridine moiety ( 197 ), instead of imidazole[1,2‐ a ]pyridine, also possessed anti‐TB activity with MIC values of 11.1 and 5.6 nM against drug‐sensitive M. tuberculosis H37Rv and H37Ra strains (Fig. ) …”
Section: Pyridinesmentioning
confidence: 99%